Pemberdayaan Sosial Berbasis Bantuan Modal : Strategi Penguatan Ekonomi Masyarakat - Fathan Hazami; Nabil Atthaillah S; Affan Khoirulramadhan; Rifma Ghulam Dzajali (Lembaga Pengembangan Kinerja Dosen, 2025)
Community empowerment is a strategy to strengthen the community's economy in order to improve the quality of life and socio-economic independence of residents, especially in areas with high poverty rates. This article aims to examine the impact of providing business capital on improving the community's economy in supporting the success of the program implemented by Muhammadiyah University Prof. Hamka. The implementation method is through a counseling approach on community empowerment. In addition, this program also encourages a sense of hard work and social solidarity. The results of the activities show an increase in socio-economics and can overcome poverty problems. Empowerment carried out by students also creates values ​​of mutual cooperation and social solidarity. Student involvement in capital assistance-based empowerment programs is a driver of economic change in society. Therefore, synergy is needed between the surrounding community and community institutions to create a just society and reduce poverty in certain areas.